Changes in Pregnant Women’s Knowledge of High-Risk Pregnancy Before and After Counseling - Mantasia R; Sumarmi; Nuryana, Riska; Hamka; Marlina, Suci (Bantayang Omni Cendekia, 2026)
Background: High-risk pregnancy is a condition that can lead to complications and threaten the health of both the mother and the fetus, potentially resulting in morbidity or mortality. Several factors contribute to high-risk pregnancy, including maternal age under 20 years or over 35 years, short birth spacing (<2 years), and grand multiparity. Objective: This study aimed to assess the level of knowledge of pregnant women regarding high-risk pregnancy before and after counseling at the Sanrobone Health Center. Methods: This study used a descriptive quantitative design with a pre–post approach. The population and sample consisted of 52 pregnant women, selected using total sampling. Data were collected using a questionnaire consisting of 20 questions related to knowledge of high-risk pregnancy, administered before and after counseling. Results: Before counseling, 8 respondents (15.4%) had good knowledge, 17 respondents (32.6%) had sufficient knowledge, and 27 respondents (52.0%) had poor knowledge. After counseling, the proportion of respondents with good knowledge increased to 21 (40.4%), those with sufficient knowledge were 26 (50.0%), and those with poor knowledge decreased to 5 (9.6%). Conclusion: Counseling significantly improved the knowledge of pregnant women regarding high-risk pregnancy. Strengthening educational interventions is essential to support early detection and prevention of pregnancy complications.